Relation between obstructive airway disease and body mass index in patients with obstructive sleep apnoea - ., Samta; Surynarayana, H. V.; Chandrashekhar, H. B.; H. L., Prasad (International Journal of Research in Medical Sciences, 2017)
Background: Obstructive airway diseases are characterized by a limitation of airflow when measured by spirometry. There is also a correlation between sleep quality and the obstructive lung diseases. Therefore, the present study was designed to assess the occurrence of obstructive airway disease by assessing body mass index, neck circumference in patients with obstructive sleep apnoea (OSA). Methods: Patients with sleep complaints undergoing Polysomnography for diagnosis of OSA in Department of Pulmonary Medicine were enrolled for the study. After the ethical clearance and informed consent, grading of breathlessness was done by MMRC Dyspnea scale. An in-house sleep questionnaire with Epworth Sleepiness scale score of 0 to 3 was administered. The clinical examination included the measurement of Body mass index, Neck circumference and Mallampatti score. The data were represented as percentages and mean + SD. Chi-square test and student‘t’ test was used to determine the statistical difference and a “p” value of less than 0.05 was considered the level of significance. Results: The PFT and age in patients with obstruction (FEV1/FVC<70) was statistically significant (p=0.011) whereas, that in patients with obstruction (FEV1/FVC<75) was statistically insignificant (p=0.843). The PFT and BMI in patients with Obstruction (FEV1/FVC<70) and (FEV1/FVC<75) was found to be statistically insignificant (p=0.869 and 0.869). Conclusions: The Patients with Obstructive airway disease also showed frequent oxygen de-saturations and had high Respiratory Distress Index. The Patients with Obstructive airway disease had severe OSA.